THE ANALYSIS OF ECONOMIC POTENTIAL IN NORTH SUMATERA PROVINCE - Ahmad Habibi Harahap; Eko Wahyu Nugrahadi (Quantitative Economics Journal, 2019)
Economic growth of North Sumatera Province is not quite on the top of optimum. If the compared by some of others province in Indonesia and by  all of his potention, the North Sumatera Province only on the 10th rank of economic growth in Indonesia in 2009-2013 period. The purpose of this study is toanalyze the economic sectors which are the basis in each district/city in North Sumatera province and to determine the structure of economic growth in the district /city both sectoral and aggregate the province of North Sumatera. Structural transformation to some extent will have an impact on overall economic growth. Analysis tools used in this study is Location Quetiont (LQ), Growth Ratio Model (MRP), overlay analysis, and shift share analysis. Results of this study showed that the agriculture sector is a sector which is the basis in nearly 13 districts/cities in North Sumatera Province. But the growth in agriculture, processing industries, mining and quarrying, and the electricity, gas & water supply sector likely slowed, otherwise all tertiary sectors which include: trade, hotels, and restaurants; transportation and communication, finance, leasing, and services company, and the services sector is likely to experience growth positive. Transportation and communication is a sector with the highest growth occurring in North Sumatera Province. Shift Share Analysis results showed that in the Province of North Sumatera is going structural transformation characterized by decreasing the role of the agricultural sector, and the increasing role of the service sector. This condition as well as contrary to the Kuznets theory which states that the process of structural transformation contribution marked by shifting agriculture to manufacturing and then to services sector.